IDENTIFICATION OF CERTAIN AGRICULTURAL TRAITS AND INTER-TRAIT RELATIONSHIPS IN THE HELIANTHEMUM LEDIFOLIUM (L.) MILLER VAR. LASIOCARPUM (WILLK) BORNM. - Basbag, Mehmet; Cacan, Erdal; Sayar, Mehmet Salih; Karan, Halil (Pakistan Botanical Soc, 2018)
This study was conducted to determine certain plant traits and inter -trait relationships in the Helianthemum ledifolium (L.) Miller var. lasiocarpum (Willk.) Bornm. which is grown naturally in the protected area at the campus of Dicle University in 2015 and 2016. Two-year average of the research showed that the plant height was 30.04 cm, the number of main stem per plant was 1.02, the main stem diameter was 1.24 mm, the number of branch per plant was 1.06, the capsule number per plant was 4.04, the capsule diameter was 7.21 mm, the seed number per capsule was 158.5, the seed weight per capsule was 0.065 g, the thousand seed weight was 0.421 g, the seed yield per plant was 0.265 g and the germination rate was 0.5%. According to analysis results belonging to dry forage of the plant, the crude protein ratio was determined as 18.79%, ADF ratio as 26.23%, NDF ratio as 49.21%, calcium ratio as 1.14%, magnesium ratio as 0.04%, phosphor ratio as 0.42% and potassium ratio as 3.79%. The correlation analysis results showed that positive and highly significant relation was found between seed yield per plant and plant height, branch number per plant, capsule number per plant, number of seeds per capsule, seed weight per capsule traits. To increase seed yield in Helianthemum genotypes, exclusively that traits should be taken into account. Results of the study indicated that forage of Helianthemum ledifolium (L.) Miller var. lasiocarpum (Willk.) Bornm had sufficient digestibility and nutrient contents for livestock. But, it is recommended that new investigations should be carried out in order to determine the content of harmful substances in the forage of these plants for safely using the forages in the livestock feeding.
Keywords: Agronomic characteristics; Correlation; Helianthemum ledifolium; Turkey